Who gives aid to whom and when? Aid accelerations, shocks and policies - Tilman Brück; Guo Xu (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
We address the pitfalls of averaging by exploiting the longitudinal variation in aid to identify sudden and sharp increases in aid flows. Focusing on specific events, we test if aid accelerations correspond to policies and shocks in the recipient country. For a large sample of 145 recipient countries and 33 donors from 1960- 2007, we find that positive regime changes and wars are significant predictors of aid accelerations. Disaggregating aid flows by donors, we find indicative evidence for competing allocation rules, particularly among European donors. We argue that drivers of aid accelerations differ from drivers of average aid flows - a distinction that can reconcile some of the ambiguous empirical results in the aid literature.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: O1; F35; F50; 330; ODA; growth accelerations; policies; Entwicklungshilfe; Industriestaaten; Schock; Krieg; Demokratisierung; Entwicklungsländer